A Study on the Views and Thoughts of Dog Owners in Turkiye on Animal Welfare - Seker, Ibrahim; Koseman, A.; Erten, O.; Ozen, A. (Gesellschaft Schweizer Tierarztinnen & Tierarzte, 2024)
The aim of the present study was to determine the views and thoughts of dog owners in Turkiye on animal welfare. The research material consisted of data obtained from face-to-face surveys with 172 randomly selected dog owners. Half of the dog owners (54,7 %) were aware of the concept of animal welfare, and almost two-thirds (61,6 %) organized their dogs' living spaces according to animal welfare principles. Participants most associated the concept of animal welfare with the concept of animal quality of life (47,7 %). Gender (p<0.01) and education level (p<0.01) had an effect on the understanding of the animal welfare concept; female and higher eductation resulted in a broader understanding. More than half of the participants (54,1 %) obtained information about animal welfare from written and visual non-evidence based media.
Une étude sur les opinions et les réflexions des propriétaires de chiens en Turquie concernant le bien-être des animaux]; [Ansichten und Überlegungen von Hundebesitzern zum Tierschutz in der Türkei]; [Uno studio sulle opinioni e i pensieri dei proprietari di cani in Turchia sul benessere degli animali
Keywords: Awareness; consciousness; thought; animal welfare; dog; dog owner